PROBLEMS IN LEARNING UZBEK FOR EUROPEAN LANGUAGE LEARNERS - Umurzakova Sevara Abdukarimovna (American Journals Publishing, 2025)
This study explores the challenges faced by European language learners in acquiring Uzbek. It examines phonetic, grammatical, lexical, and cultural difficulties that arise due to structural differences between Uzbek and Indo-European languages. Particular attention is given to vowel harmony, agglutinative morphology, and the absence of articles, which contrast with European linguistic norms. Additionally, sociolinguistic factors, such as exposure to Uzbek language materials and native speaker interaction, are considered. The findings aim to provide insights for developing more effective Uzbek language learning strategies for European learners.
Keywords: Uzbek language, European learners, phonetic difficulties, grammatical challenges, agglutinative structure, vowel harmony, second language acquisition, language learning strategies.